Antimicrobial Resistance Patterns in Organic and Conventional Dairy Herds in Sweden - Karin Sjöström; Rachel A. Hickman; Viktoria Tepper; Gabriela Olmos Antillón; Josef D. Järhult; Ulf Emanuelson; Nils Fall; Susanna Sternberg Lewerin (MDPI AG, 2020)
Monitoring antimicrobial resistance (AMR) and use (AMU) is important for control. We used Escherichia coli from healthy young calves as an indicator to evaluate whether AMR patterns differ between Swedish organic and conventional dairy herds and whether the patterns could be related to AMU data. Samples were taken twice, in 30 organic and 30 conventional dairy herds. Selective culturing for Escherichia coli, without antibiotics and with nalidixic acid or tetracycline, was used to estimate the proportions of resistant isolates. Microdilution was used to determine the minimum inhibitory concentrations (MICs) for thirteen antimicrobial substances. AMU data were based on collection of empty drug packages. Less than 8% of the bacterial growth on non-selective plates was also found on selective plates with tetracycline, and 1% on plates with nalidixic acid. Despite some MIC variations, resistance patterns were largely similar in both periods, and between organic and conventional herds. For most substances, only a few isolates were classified as resistant. The most common resistances were against ampicillin, streptomycin, sulfamethoxazole, and tetracycline. No clear association with AMU could be found. The lack of difference between organic and conventional herds is likely due to a generally good animal health status and consequent low AMU in both categories.